Side effects of anabolic-androgenic steroids abuse – empirical research based on anonymous surveys among people who regularly attend the gym - Pająk, Monika; Grużewska-Piotrowska, Kinga; Hubka, Joanna; Grużewska, Agnieszka (Quality in Sport, 2023)
Introduction: The use of anabolic androgenic steroids is particularly common in regular gyms and fitness centres participants. AAS are usually synthetic derivatives of testosterone with anabolic and androgenic effect. However, many people, including AAS users, do not realize how many side effects they can cause. The aim of the study: The aim of the study was to assess if people who regularly attend to the gym are aware of the side effects of using anabolic steroids by empirical research based on anonymous surveys. Materials and methods: The research material was collected using an anonymous online survey in April 2023. The obtained results were analyzed and verified on the basis of scientific literature and statistically processed using Microsoft Office Excel. Results: Of the 112 gym participants, 20,5% reported using anabolic-androgenic steroids in the past. Most of the people filling the questionnaire are aware of the negative health effects of AAS use. However, most of them can’t name more than 4 side effects, which shows that knowledge about AAS is still unexplored by this social group. Conclusion: The use of anabolic androgenic steroids to increase muscle size and strength is widespread. Various side effects are very common when using AAS, some of them can seriously affect the health of the users. By raising awareness of side-effects that AAS can cause, it is possible to discourage many people from using these performance-enhancing substances. Keywords: Anabolic-androgenic steroids, testosterone, gym, doping, bodybuilding